HDL protein composition alters from proatherogenic into less atherogenic and proinflammatory in rheumatoid arthritis patients responding to rituximab. Issue 4 (15th May 2012) - Raterman, Hennie G; Levels, Han; Voskuyl, Alexandre E; Lems, Willem F; Dijkmans, Ben A; Nurmohamed, Michael T
Abstract : Objective: An atherogenic lipid profile is an established risk factor for cardiovascular (CV) diseases. Interestingly, high inflammatory states as present in rheumatoid arthritis (RA) are associated with unfavourable lipid profile. Data about effects of novel immunomodulating agents as rituximab (RTX) on lipid profile are limited. Therefore, changes in lipids in RTX treated RA patients were evaluated. Methods: In 49 consecutive RTX treated RA patients, serum and EDTA plasma samples were collected at baseline, 1, 3 and 6 months. In these samples, lipid and levels were assessed to determine changes in time. Surface-enhanced laser desorption/ionisation time-of-flight (SELDI-TOF) MS analysis was performed in six good and six non-responding RA patients to study functional high density lipoprotein (HDL) protein composition changes in time. Results: In the total group (n=49), the atherogenic index decreased from 4.3 to 3.9 (∼9%) after 6 months. Testing for effect modification revealed a difference in the effect on lipid levels between responders and non-responders upon RTX (p<0.001). ApoB to ApoA-I ratios decreased significantly (∼9%) in good responding (n=32) patients. SELDI-TOF MS analysis revealed a significant decrease in density of mass charge (m/z) marker 11743, representing a decrease in serum amyloid A, in good responding patients. Conclusion: This study indicates beneficial effects on cholesterol profile upon RTX treatment along with improvement of disease activity. Proteomic analysis of the HDL particle reveals composition changes from proatherogenic to a less proatherogenic composition during 6 months RTX treatment. Whether these HDL particle alterations during immunotherapies result in a lower CV event rate remains to be established.